The relationship between emotional intelligence and self-directed learning readiness among students in the faculty of medicine - Eko Novanto Nurismail; Dyah Gita Rambu Kareri; Derri Riskiyanti Tallo Manafe; I Made Artawan (Program Studi bimbingan Konseling PPs UNM Makassar, 2021)
This study is aimed to investigate the relationship between emotional intelligence and self-directed learning readiness (SDLR) among students in Faculty of Medicine, University of Nusa Cendana. This analytical observational research implemented cross sectional design with stratified random sampling technique on preclinical medical students at the Faculty of Medicine, University of Nusa Cendana, in the academic years of 2017, 2018, and 2019. A total of 156 respondents which fulfilled the inclusion criteria were recruited in this study by filling questionnaires of Schutte emotional intelegence scale (SEIS) and self-directed learning readiness scale (SDLRS) analyzed using Somer’s d test. The results of the study showed that: (1) there is a significant relationship between emotional intelligence and SDLR of the students at the Faculty of Medicine, University of Nusa Dua (p<0.05) with strong correlation coefficient (r: 0.534); (2) there were 127 preclinical medical students (81.41%) with a high level of emotional intelligence and 29 preclinical medical students (18.59%) had a moderate level of emotional intelligence, but none of them had a low level of emotional intelligence; and (3) there were 84 preclinical medical students (53.84) who had high level of SDLR and 72 (46.16%) with a moderate level of SDLR, but none of them had a low SDLR level.